Cutaneous metastasis of rectal adenocarcinoma: a case report and literature review - Alina, Vesa; Maghiar, Octavian; Maghiar, Laura; Cuc, Romina; Pop, Ovidiu; Pascalau, Andrei; Boros, Monica; Maghiar, Adrian (Polish Journal of Pathology, 2023)
According to the latest data provided by Globocan 2020, the incidence of colorectal cancer ranks third, after lung cancer and breast cancer, becoming a more and more important global health issue. Of the cases diagnosed with colorectal cancer, more than 25% are diagnosed in the metastatic stage, with the presence of secondary tumors more frequently in the liver, lung and bone. Skin metastases from colorectal cancer are still rare today (< 4%). We want to present a rare, unique case in our department of a 74-year-old patient diagnosed 9 years ago with a malignant rectal tumor who, after a disease-free period of approximately 8 years and a half, developed multiple skin metastases of rectal adenocarcinoma.